PEMODELAN NILAI TANAH DI KAWASAN WISATA SENGGIGI LOMBOK BARAT NTB - , AIZZAT ABD FATTAH; , Ir. Waljiyanto M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Development of tourism zone is followed by construction of infrastructure, especially hotels and support facilities. On the process of construction is indicating high transaction on last five years. Sustainable development is directly proportional to increas demand for land , that caused a significant increase in the value of tourism zone , as well as the area of research that has taken place Senggigi tourist zone of West Lombok NTB . The purpose of this research is to create a modell of land value which this product is showed in Land Value Map Senggigi Tourism Zone of West Lombok NTB 2014. Appraisal valuation methode in this reseach used sales comparision approach,where the land parcel that will be appraised was compared with other s imilar land parcel have sale values already known. It was valued by a mass appraisal . The data of trading used 41 time as long Januari 2013 up to Agustus 2013,which was obtained from the montly report of Pejabat Pembuat Akta Tanah (PPAT) to the office of Dinas Pendapatan dan Pengelolaan Keuangan Aset Daerah (DPPKAD) West Lombok NTB. The analysis was done by using multiple linier regresision analysis on Microsoft Excel 2007 . the dependent variabel were the land value and independent variabel is large of parcel,distance to main road, distance to beach and distance to center of economic. Calculation the land values grounded on result modelling used Microsoft Excel 2007. The making Land Value Map of Senggigi tourism zone of West Lombok NTB 2014 used ArcGIS 9.3. The result of this reseach is Land Value Map of Senggigi tourism zone of West Lombok NTB 2014 is 11 clasess. The result of multiple linier regression analysis showed that value of Coefficients of Variation ( COV) as model quality tes 17 % and Price Related Differential 0.98. This matter showed that the appraisal model is accepted and can be applied to this area of research.